Conceptual Principles of Education for Sustainable Development - Karpan, Iryna; Chernikova, Nataliia; Motuz, Tetiana; Bratanich, Boris; Lysokolenko, Tetiana (European Journal of Sustainable Development, 2020)
Education has an important place in transitional strategy of society to sustainable development that is proved by many international acts. In the outlines of modern approaches, education for sustainable development is characterized as innovative concept of changes to educational activity, as mechanism of realization of strategy of sustainable development, as instrument of modernization of educational practice, as one of the basis of modern educational quality and continuity standards. National system of global aims for consolidation of society of sustainable development with an accent on the significance of educational matter was created in Ukraine. Education for sustainable development is characterized by being part to structure creating social institutes of modern society, transversality, subjective direction, integrativity, forward-looking character. This vector of education research is same with global man’s intentions of civilization development – increase in human’s value in all spheres of life, developing of democratic management, constructive cooperation and communication, etc. Among multidimensional potential of researched phenomenon the most practical value has environmental education. As for today, environmental education is a practical mechanism of transformation of educational system on the principles of sustainable development. Environmental education is seen as an instrument for systematic formation of man’s basic attributes for being part of education for sustainable development field – critical thinking, environmental worldview, subjective-value approach to environment, eco-cultural values. Cumulative result of environmental education is formation of environmental culture. Key words: education, sustainable development, environment, ecology, synergetic, culture, humanism.